2020
DOI: 10.1177/1363459320976752
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial challenges and concerns of COVID-19: A qualitative study in Iran

Abstract: As the world struggles to cope with the COVID-19 pandemic, it is critical that the psychosocial aspects related to health are attended to in addition to biological aspects. To this end, the present study aimed to explore the challenges and concerns facing people affected by COVID-19. This qualitative study was conducted using the content analysis method. A total of 25 people affected by COVID-19 were selected purposefully and administered semi-structured interviews. The sampling continued until data saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
9
11
0
1
Order By: Relevance
“… 10 Further, our findings regarding the need for emotional connection and intimacy provide support for recent qualitative research into the impact of COVID-19 and adherence to government guidance, which showed that some may only partially adhere to the behaviours due to the need for and cultural importance of social contact, and some reported feelings of loss and grief over the loss of social interaction during lockdown. 21–23 Concerns about the negative impact of self-isolation, both in terms of practical logistics and emotional well-being, were also raised in a qualitative study with people who had been in contact with someone with COVID-19. 24 This suggests that self-isolation is a very difficult behaviour for many people even when risk is known to be high, and that appropriate support is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Further, our findings regarding the need for emotional connection and intimacy provide support for recent qualitative research into the impact of COVID-19 and adherence to government guidance, which showed that some may only partially adhere to the behaviours due to the need for and cultural importance of social contact, and some reported feelings of loss and grief over the loss of social interaction during lockdown. 21–23 Concerns about the negative impact of self-isolation, both in terms of practical logistics and emotional well-being, were also raised in a qualitative study with people who had been in contact with someone with COVID-19. 24 This suggests that self-isolation is a very difficult behaviour for many people even when risk is known to be high, and that appropriate support is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the need for clarity and consistency in government and public health guidance has also been highlighted in other studies as important in aiding the public to adhere to infection control behaviours. 21 23 25 …”
Section: Discussionmentioning
confidence: 99%
“…In principle, the integration of PP2.0 into a broader salutogenic framework for psychological intervention, particularly in the context of COVID-19, has many advantages over conventional approaches. The development of a formal therapeutic model or manual for such an intervention would require further inputs from a wide range of stakeholders, including (1) direct perspectives from persons affected by the pandemic across countries and cultures (Alipour et al, 2020;Mazumder et al, 2021); (2) discussions with healthcare workers handling mental health issues during the pandemic, to outline their perceptions of the "conventional" psychiatric approach and the limitations thereof (Bommersbach et al, 2021); (3) expert opinions from specialists already involved in interventions based on a salutogenic, PP2.0, or person-centered approach (Christodoulou et al, 2018;Wong, 2020); (4) inputs from local community and spiritual leaders, to identify those aspects of meaningfulness and coherence that are culturally relevant and could foster resilience (Thompkins et al, 2020); (5) the perspectives of social science experts and policy makers on which systemic interventions could foster a SOC and strengthen resistance resources (Christodoulou et al, 2018;Alvarez et al, 2020); (6) specific advice from experts in information technology, in order to devise optimal strategies on adapting salutogenic-PP2.0 principles to interventions delivered via mobile or social media platforms (Goransson et al, 2020), and (7) careful planning of intervention trials in collaboration with experts in biostatistics and research methodology, to avoid the methodological flaws that affected earlier studies in this field (Alvarez et al, 2020). It is hoped that the preliminary steps outlined in this paper are of use not only to researchers, but to clinicians and those involved in formulating policies to help those most affected by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Another metaphor subtheme determined in this theme was concepts related to diseases and within this scope, nurses were mostly determined to use metaphors related to diseases like flu and cancer. Alipour et al ( 2020 ), Moradi et al ( 2020 ) and Galehdar et al ( 2020 ) determined that individuals, participating in their qualitative studies completed with the aim of determining psychological changes induced in individuals by COVID‐19, defined COVID‐19 as a difficult and unpredictable disease process. It is a normal situation that this process, which affects the whole world and many people both physically and psychologically, is perceived by nurses as a widespread disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another metaphor subtheme determined in this theme was concepts related to diseases and within this scope, nurses were mostly determined to use metaphors related to diseases like flu and cancer. Alipour et al (2020), Moradi et al (2020) and Galehdar et al (2020)…”
Section: Discussionmentioning
confidence: 99%